Water Quality of Freshwater Ecosystems in a Temperate Climate - Gołdyn, Ryszard; Klimaszyk, Piotr (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
This Special Issue consists of fourteen original scientific articles concerning different problems associated with the water quality of freshwater ecosystems in a temperate climate. Most of the articles deal with the relationship between water quality and the structure of ecosystem biocenoses. The conclusion of these articles confirms the fact that the deterioration of water quality has a direct impact on the quantitative and qualitative structure of biocenoses. This is accompanied by a decline in biodiversity and the disappearance of rare plant and animal species. They also draw attention to the particular importance of internal physical and chemical differentiation within the aquatic ecosystem, both in horizontal and vertical dimensions. The problem of ensuring proper ecological conditions and good quality of water in freshwater aquatic ecosystems is also raised, and various methods for the restoration of water bodies are presented. This Special Issue contributes to a better understanding of the causes of water quality deterioration, the mechanisms responsible for the functioning of ecosystems, including the decrease of biodiversity and the possibilities of improving their condition. Thus, it can be helpful for regaining the good ecological status of water bodies required by the Water Framework Directive.